The sum of -19ab and 7ab = -19ab + 7ab = -12ab
the sum of -11ab and -23ab = -11ab + (-23ab) = - 34ab
So
<span>Subtract the sum of -11ab and -23ab from the sum of -19ab and 7ab:
</span> (-12ab) - (-34ab) = -12ab + 34ab = 22ab
Answer
22ab
Answer: 3
Step-by-step explanation: 2+1=3
Answer:
I agree with both of them
Step-by-step explanation:
A dozen is 12 muffins. Therefore, you pay $3.00 for 12 muffins.
We know that you pay $3.00 for 12 muffins we need to find out how much EACH muffin cost. For that we need to divide $3.00 by 12 which is 0.25.
Now we need to know how much it will cost us for 16 muffins. We use our equation 16*0.25 which is 4. Elena said she will pay 4 so she is right.
Andre said he will buy 8 muffins so we use our equation again 8*0.25 which is 2. He said he will pay 2 so he is right.
Let's solve your equation step-by-step.<span><span><span><span>6n</span>+n</span>+14</span>=0</span>
Step 1: Simplify both sides of the equation.<span><span><span><span>6n</span>+n</span>+14</span>=0</span><span>Simplify: (Show steps)</span><span><span><span>7n</span>+14</span>=0</span>
Step 2: Subtract 14 from both sides.<span><span><span><span>7n</span>+14</span>−14</span>=<span>0−14</span></span><span><span>7n</span>=<span>−14</span></span>
Step 3: Divide both sides by 7.<span><span><span>7n</span>7</span>=<span><span>−14</span>7</span></span><span>n=<span>−2</span></span>
Answer:<span>n=<span>−<span>2</span></span></span>
Answer:
that is called a repeating decimal.
Step-by-step explanation: